2017
DOI: 10.4049/jimmunol.1601441
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Dependent Insulinotropic Polypeptide Receptor Deficiency Leads to Impaired Bone Marrow Hematopoiesis

Abstract: The bone marrow (BM) contains controlled specialized microenvironments, or niches, that regulate the quiescence, proliferation, and differentiation of hematopoietic stem and progenitor cells (HSPC). The glucose-dependent insulinotropic polypeptide (GIP) is a gut-derived incretin hormone that mediates postprandial insulin secretion and has anabolic effects on adipose tissue. Previous studies demonstrated altered bone microarchitecture in mice deficient for GIP receptor ( ), as well as the expression of high-aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Since recent work by Mantelmacher et al. found GIP to increase bone marrow hematopoiesis with the consequence of elevated numbers of differentiated blood leukocytes in mice [15] , we speculate that changes in blood monocytes might not explain our phenotype. Here we found GIP to decrease hepatic proinflammatory cyto- and chemokine levels and to directly inhibit CCR2 expression in monocytes, which was linked to blocked MCP-1-induced monocyte migration In vitro.…”
Section: Discussionmentioning
confidence: 70%
“…Since recent work by Mantelmacher et al. found GIP to increase bone marrow hematopoiesis with the consequence of elevated numbers of differentiated blood leukocytes in mice [15] , we speculate that changes in blood monocytes might not explain our phenotype. Here we found GIP to decrease hepatic proinflammatory cyto- and chemokine levels and to directly inhibit CCR2 expression in monocytes, which was linked to blocked MCP-1-induced monocyte migration In vitro.…”
Section: Discussionmentioning
confidence: 70%
“…Analysis of Sca-1 + CD117 + cells within the Lineage neg population showed that PBS-treated CIA animals had an increased proportion of HSCs in the BM compared to both naïve and ES-62-treated CIA animals (Figure 1 F). The BM HSC population is supported and maintained by stromal and OB production of OPN, but analysis of OPN mRNA in the bone-lining cells ( 23 ) of the femurs and tibias showed that OPN mRNA levels were not significantly different in PBS-treated CIA mice relative to naïve and ES-62-treated CIA animals (Figure 1 G). As ES-62 is able to return HSC levels to those found in healthy animals and show evidence of reducing cathepsin K + OC numbers in the joints of arthritic mice, we next aimed to determine specifically whether CIA would affect defined OC progenitor populations in the BM.…”
Section: Resultsmentioning
confidence: 99%
“…BM cells (10 6 ), or OCs that were pre-treated with SMAs (5 µg/ml) for 24 h, were lysed in RNeasy lysis buffer prior to mRNA extraction using an RNeasy Plus Mini kit (Qiagen, Germany) according to manufacturer’s instructions. Additionally, cleaned and flushed femurs and tibias were then flushed with QIAzol to obtain RNA from bone-lining cells as previously described ( 23 ). cDNA was generated using a high capacity cDNA Reverse Transcriptase kit (Applied Biosystems, Life Technology) before use in PCR amplifications using the StepOne Plus™ real-time PCR system (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…The BM contains controlled specialized microenvironments, or niches, that regulate the quiescence, proliferation, and differentiation of hematopoietic stem and progenitor cells (HSPC). Given the expression of GIPR in cells constituting the BM HSPC niche and the altered architecture and matrix of Gipr −/− bones, we endeavored to study the regulation of BM hematopoiesis by GIP [172]. Indeed, we have shown that GIP supports BM hematopoiesis through its regulation of the hematopoiesis-supportive activity of stromal cells composing the BM HSPC niche [172], therefore suggesting another layer by which GIP may modulate immune responses.…”
Section: Gip-immunoregulatory Functionsmentioning
confidence: 99%
“…Given the expression of GIPR in cells constituting the BM HSPC niche and the altered architecture and matrix of Gipr −/− bones, we endeavored to study the regulation of BM hematopoiesis by GIP [172]. Indeed, we have shown that GIP supports BM hematopoiesis through its regulation of the hematopoiesis-supportive activity of stromal cells composing the BM HSPC niche [172], therefore suggesting another layer by which GIP may modulate immune responses. While it is well-established that inflammation increases GLP-1 levels, how inflammatory stimuli mediate GIP secretion remains largely unknown.…”
Section: Gip-immunoregulatory Functionsmentioning
confidence: 99%